Web-Based Pharmacoinformatics Platform for Generic Drug Information in Gorontalo, Indonesia - Paneo, Mohamad Aprianto; Tuloli, Teti Sutriyati; Nakoe, Moh Rivai; Pakaya, Nikmasari; Thomas, Nurain; Anggai, Rifka Anggraini; Latif, Multiani S. (Sciences of Pharmacy, 2025)
This study aims to evaluate the effectiveness of a web-based drug information application in providing accessible and reliable drug-related information to the public in Gorontalo Province, Indonesia. A prospective, non-randomized study was conducted with 205 participants from the Gorontalo community. Participants completed a structured questionnaire assessing their experience with the "Cari Obatmu" feature on the Ikatan Apoteker Indonesia (IAI) Gorontalo website. The questionnaire covered various aspects such as user interface, search efficiency, clarity of drug indications, side effects, and usability. Descriptive statistics, Cronbach's Alpha for reliability, One-Way ANOVA for demographic differences, and effect size analysis were used in data analysis. The findings indicated high user satisfaction, with mean scores ranging from 4.16 to 4.28 across different aspects assessed. A Cronbach’s Alpha value of 0.975 confirmed excellent internal consistency of the data. The One-Way ANOVA analysis revealed no significant differences in satisfaction scores among demographic groups (p = 0.636), with effect sizes being minimal. The web-based drug information application was well-received, particularly for its functionality and ease of use. However, further improvements are necessary to enhance user experience and feature development. These findings highlight the potential to expand web-based drug information tools to improve public health outcomes in Indonesia, considering the diverse demographic and user needs.